Characteristics of spatial distribution of creative industries in Ljubljana and the Ljubljana region - Uršič, Matjaž (Acta geographica Slovenica, 2016)
This article analyzes the key features of the spatial distribution of creative industries in Ljubljana and the Ljubljana urban region. Special attention is devoted to analyzing factors that influence the concentration of individual branches of creative industries in specific locations. GIS tools were applied to evaluate factors that influence the distribution of creative activities. Simultaneously, the concept of central places is used to analyze variations of spatial clustering of creative enterprises. Data for the analysis were collected from the Slovenian Business Register (AJPES) and the Real Estate Register (GURS). The mapping of creative economies identifies patterns of concentration and reveals some locational disadvantages that have arisen due to the absence of clear development strategies regarding creative economies in Slovenia.
Keywords: grozdenje; koncentracija; Ljubljana; prostorski razvoj; urbani prostor